Electrochemical Corrosion Behaviour Analysis of Mg-Alloys Used for Orthopaedics and Vascular Implants. Issue 1 (1st February 2022) - Kumar, Rohit; Katyal, Puneet; Gupta, Munish; Singh, Vijender
Abstract: Mg-alloys having bone liked mechanical properties are biodegradable, biocompatible and osteoconductive metallic materials are potential candidates used for orthopaedics and vascular implants. Therefore, present experimentation is an effort to analyse the corrosion behaviour of Mg based alloys such as AZ81 and ZM21 for their usage as bio-degradable implant materials. The corrosion behaviour is analysed using the electrochemical workstation. SEM and EDS are used for high-resolution images and composition of magnesium-based alloys. Using Potentiodynamic polarization curves and Nyquist plots, corrosion rates were observed for 3.0 hours studies on ZM21(193.53 mm/year) and AZ81 (24.22 mm/year) for Mg-alloys. AZ81 shows higher corrosion resistance than ZM21. The results of these experimental findings may be helpful for the designers and researchers in selecting and improving the clinical performance of Mg-based implants for biomedical applications.